Engineering Chimeric Antigen Receptor T-Cells for Racing in Solid Tumors: Don’t Forget the Fuel - Irving, Melita; Vuillefroy de Silly, Romain; Scholten, Kirsten; Dilek, Nahzli; Coukos, George (Frontiers in Immunology, 2017)
T-cells play a critical role in tumor immunity. Indeed, the presence of tumor infiltrating lymphocytes is a predictor of favorable patient prognosis for many indications, and is a requirement for responsiveness to immune checkpoint blockade therapy targeting PD-1. For tumors lacking immune infiltrate, or for which antigen processing and/or presentation has been downregulated, a promising immunotherapeutic approach is CAR T-cell therapy. CARs are hybrid receptors that link the tumor antigen specificity and affinity of an antibody-derived single chain variable fragment with signaling endodomains associated with T-cell activation. CAR therapy targeting CD19 has yielded extraordinary clinical responses against some hematological tumors. Solid tumors, however, remain an important challenge to CAR T-cells due to issues of homing, tumor vasculature and stromal barriers, and a range of obstacles in the tumor bed. Protumoral immune infiltrate including T regulatory cells and myeloid derived suppressor cells have been well characterized for their ability to upregulate inhibitory receptors and molecules that hinder effector T-cells. A critical role for metabolic barriers in the tumor microenvironment is emerging. High glucose consumption and competition for key amino acids by tumor cells can leave T-cells with insufficient energy and biosynthetic precursors to support activities such as cytokine secretion, and lead to a phenotypic state of anergy or exhaustion. CAR T-cell expansion protocols that promote a less differentiated phenotype, combined with optimal receptor design and co-engineering strategies, along with immunomodulatory therapies that also promote endogenous immunity, offer great promise in surmounting immunometabolic barriers in the tumor microenvironment and curing solid tumors.